Analisis Pengaruh Promosi Penjualan terhadap Loyalitas Pelanggan dengan Peran Mediasi Kepuasan Pelanggan Pada Layanan Go-Food di Surabaya - Hilman Syahmi Taris; Sugeng Purwanto (J-MAS (Jurnal Manajemen dan Sains), 2022)
Currently, technology is not only a complement to the business, but also the main point so that businesses can develop and be able to compete. The development of the internet at this time has changed the pattern of consumer behavior that is carried out offline in selling their products, now turning into selling products online. Apart from being a product, online marketing also applies to services and services. One example is the Gojek company, which is now a start-up in the transportation sector. This study aims to analyze the effect of sales promotion and customer satisfaction on customer satisfaction and customer loyalty and to examine the Mediation Role of Customer Satisfaction on the Relationship between Promotion and Customer Loyalty on Go-Food Services in Surabaya. in this study used the variables of Sales Promotion, Customer Satisfaction, and Customer Loyalty. The measurement scale used in this study is the scale-weighting technique (Likert). The population in this study were all Go-Food service users in Surabaya, while the research sample was taken using a non-probability sampling technique so that 130 people were obtained. Furthermore, the data collection method used was by distributing questionnaires containing questions addressed to the sample (other people) who were used as respondents to answer these questions. In addition, the data analysis technique used in this research is Validity Test and Reliability Test using Partial Least Square (PLS) on Outter Model Test and Inner Model Test. The results of this study found that the sales promotion variable was able to support the customer satisfaction of Go-Food services in Surabaya. Promotional variables have not had an overall effect on customer loyalty for Go-Food services in Surabaya. Furthermore, the customer satisfaction variable is able to increase customer loyalty for Go-Food services in Surabaya. Then the customer satisfaction variable is able to mediate the sales promotion variable so that it can lead to customer loyalty for Go-Food services in Surabaya